2022
DOI: 10.1017/jns.2022.49
|View full text |Cite
|
Sign up to set email alerts
|

The association between the Healthy Eating Index (HEI-2015) score and body composition among Iranian soccer players and referees: a cross-sectional study

Abstract: For an optimal performance, soccer players and referees need to consume a high-quality diet. The Healthy Eating Index (HEI) is a tool that can estimate diet quality and has been shown to be associated with body composition. The aims of the present study were first to determine the HEI-2015 score of the diets consumed by athletes and second its association with different body composition parameters of athletes. We conducted a cross-sectional study on 198 soccer players and referees. Dietary intakes were recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Their results showed that HEI was significantly correlated with the percentage of muscle mass, WHR, and total body fat (TBF) in male referees and football players. Additionally, in the study mentioned above, consistent with the present study, the HEI scores showed moderate quality of the diet [ 21 ]. Therefore, encouraging football athletes to improve their diet quality can be considered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Their results showed that HEI was significantly correlated with the percentage of muscle mass, WHR, and total body fat (TBF) in male referees and football players. Additionally, in the study mentioned above, consistent with the present study, the HEI scores showed moderate quality of the diet [ 21 ]. Therefore, encouraging football athletes to improve their diet quality can be considered.…”
Section: Discussionsupporting
confidence: 91%
“…The importance of diet quality for football players has been indicated, as explained earlier [ 21 , 22 ]. Additionally, to our knowledge, no research has been conducted on the relationship between diet quality and oxidative status among footballers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The referee's performance is influenced by factors such as physical training, eating behaviours and body composition ( 1 ) . Diet quality affects body composition ( 5 ) . To maintain and improve their performance, soccer referees are recommended to consume a high-quality diet, to have optimal body composition.…”
Section: Introductionmentioning
confidence: 99%